Towards effective governance of information in a Brazilian Agricultural Research Organisation. - BERTIN, P. R. B. (2014)
There are three different uses of the term 'inoformation' in ordinary language: in the restricted sense, it means diverse types of material objects, such as data or documents ('information-as-thing'); alternatively, the term is used as in reference to the act of informing or becoming informed ('information-as-process'), or to equatge to knowledge ('information-as-knowledge'). Each of these connotations represents a legitimate view of information in its own right, being equally significant to information-intensive organisations. The literature lacks studies that approach information from an integrative viewpoint, however. The purpose of this study was to explore and develop the notion of 'information governance' as an integrative, systemic approach to information in the context of rsearch organisations. Soft Systems Methodology was used in a case study involving the Brazilian Agricultural Research Corporation. Qualitative data was gathered through in-depth interviwes with researchers and information/knowledge managers, followed by a thematic, two-level analysis. From a 'macro-level' of analysis (the wider Brazilian agricultural research system) it was found that, to solve increasingly complex research problems, collaborative, multidisciplinary networking is needed. On the other hand, competitive forces are continuously emanating from the systems of research steering, funds and resources' allocation, quality control, and recognition and reward. This confict inhibits the collaborative sharing of 'information-as-thing' and '-as-knowledge', disturbs internal communication flows and contributes to low levels of synergy and cross-departmental partnerships, ultimately affecting resarch outcomes. At a 'meso-level' (the local practices and culture of agricultural knowledge production), defferent epistemic cultures were identified (named in vitro, in situ and in silico research), which respond defferently to the oppsing forces of collaboration and competition. Based on a deep understanding of the agricultural research system and underlying epistemic cultures, a framework for effective governance of information was developed. Action to improve the governance of information at Embrapa would involve nurturing and information culture that supports collaborative work. given that interactions between researchers are determined by their individual pursuits and struggles, this would require a change in the corporate system of performance evaluation and reward, according to different epsitemic cultures.